Genetically Based Physiological Responses to Overwinter Starvation in Gibel Carp (Carassius gibelio) - Xu, Wenjie; Li, Hongyan; Wu, Liyun; Dong, Bo; Jin, Junyan; Han, Dong; Zhu, Xiaoming; Yang, Yunxia; Liu, Haokun; Xie, Shouqi (Frontiers in Endocrinology, 2020)
During the winter, fish are under the double stress of starvation and low temperatures. In previous studies, two widely cultured gibel carp strains (strain A and strain F) showed differences in lipid and glucose metabolism. Therefore, we hypothesized that the physiological changes during the overwintering period would be different between the two strains. Thus, the two strains were starved for 77 days, after which the levels of glucose and lipid metabolism, ER stress, autophagy, and apoptosis were determined. The starvation increased hepatic glycogenesis and fatty acid β-oxidation but suppressed lipogenesis, ER stress, autophagy, and apoptosis in both strains. Considering the effects of genotype, strain F had higher levels of ER stress but lower levels of autophagy and apoptosis than strain A, suggesting that strain F might be more resistant to starvation and cold stress. The interactions between strains and starvation periods were observed in plasma triglyceride contents and the mRNA levels of pyruvate kinase (pk), sterol regulatory element binding protein 1 (srebp1), activating transcription factor 4 (atf4) and autophagy protein 12 (atg12). In conclusion, long-term starvation during winter could induce hepatic glycogenesis and fatty acid β-oxidation but suppress lipogenesis, ER stress, autophagy, and apoptosis in gibel carp, and strain F may be more resistant to starvation during winter. Taken together, these results discovered the responses to prolonged starvation stress during winter in two strains of gibel carp and could provide information for genotype selection, especially for selecting strains better adapted to winter.